SN2-mediated decoupled precursor provision enables large-scale production of monodisperse lead halide perovskite quantum dots in a single reactor - Kim, Jigeon; Kim, Woongchan; Jang, Jin Il; Kim, Wooyeon; Yoo, Doheon; Kim, Jae Woo; Lee, Yubin; Choi, Min Jae; Choi, Jongmin; Kim, Hyung Min; Cho, Sung Beom; Ko, Min Jae; et al. (Advanced Composites and Hybrid Materials, 2025)
Quantum-confined lead-halide perovskite nanocrystals (QPNCs) are a promising optoelectronic semiconductor owing to their exceptional fluorescence and the size- and dimension-tunable optical properties. QPNCs having low formation energy encounter challenges in accurately regulating the nucleation and crystal growth stages during injection-based syntheses using lead halide reagents. Here, we introduce a non-injection, one-pot synthetic approach based on bimolecular nucleophilic substitution (SN2) and thermolysis reactions of the decoupled metal and halide precursors for the large-scale production of monodisperse CsPbX3-QPNCs (X = Cl, Br, I). This approach facilitates a homogeneous supply of halide anions and metal cations, enabling the precise control over the nucleation and crystal growth stages in the isolated size-focused region. Monodisperse CsPbX3-QPNCs achieve high color purity across the RGB color gamut by adjusting size, dimensionality, and halide composition, and can be produced on an ultra-large scale.
Keywords: Alkylhalides; Growth stages; Halide perovskites; Large scale productions; Large scale synthesis; Mono-disperse; Nucleation and crystal growth; Nucleophilic substitution reactions; Perovskite nanocrystal; Single reactor; Alkyl halides; Large-scale synthesis; Nucleation and crystal growth; Nucleophilic substitution reactions; Perovskite nanocrystals